Membudayakan Moderasi Melalui Program Penguatan Moderasi Beragama - Listiawati , Ni Putu (Jurnal Penelitian Agama Hindu, 2022)
The rise of religious and cultural intolerance, conflict between and among religious adherents, and even the nation's disintegration have given rise to a national program to strengthen religious moderation. Aims to examine and describe the culture of moderation in planning to strengthen religious moderation, describe the approach to the culture of moderation in program implementation, and analyze the monitoring and evaluation of program implementation carried out by the Hindu Community Guidance Sector work unit of West Nusa Tenggara Province. To answer these three objectives, 3 (three) theories are used: contingency approach, systems theory, and Anthony Giddens' structuration theory. This study uses a qualitative phenomenological paradigm. Technique for determining informants purposively with criteria, as participants, committee, planner, and person in charge. It can be concluded: 1) cultivating moderation in the planning of the program to strengthen religious moderation in the work unit of the Hindu Guidance Division of West Nusa Tenggara Province, targeting the strengthening of the Pancasila ideology in the nation and state and strengthening Hindu values that are inspired by religious moderation; 2) the implementation approach cultivates moderation, not yet innovative. The participants involved were still homogeneous. The program's target is still limited to understanding tolerance and not yet formulating a model of tolerance for a multicultural society; 3) monitoring and evaluating the cultivation of moderation in the Hindu Guidance Sector of the Regional Office of the Ministry of Religion of NTB Province using the Formative Summative Evaluation Model. It can be recommended: 1) the proposed program is expected to be more innovative, 2) religious moderation agencies (subjects) should involve a lot of leadership elements at the spearhead (close to the community), and be heterogeneous.